2010
DOI: 10.1063/1.3491470
|View full text |Cite
|
Sign up to set email alerts
|

Release monitoring of single cells on a microfluidic device coupled with fluorescence microscopy and electrochemistry

Abstract: A method for monitoring the biological exocytotic phenomena on a microfluidic system was proposed. A microfluidic device coupled with functionalities of fluorescence imaging and amperometric detection has been developed to enable the real-time monitoring of the exocytotic events. Exocytotic release of single SH-SY5Y neuroblastoma cells was studied. By staining the cells located on integrated microelectrodes with naphthalene-2,3-dicarboxaldehyde, punctuate fluorescence consistent with localization of neurotrans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…12, 13 A microfluidic device coupled with functionalities of fluorescence imaging and amperometric detection has been developed to enable the real-time monitoring of the exocytotic events of single SHSY5Y neuroblastoma cells. 14 Sigworth’s group at Yale fabricated poly(dimethyl siloxane) (PDMS) substrates to replace the pipette and successfully recorded single ion channel current from Xenopus oocytes. 15 Fertig and colleagues reported a planar patch-clamp glass chip to record electrical current measure from different cell types in a whole-cell mode.…”
Section: Introductionmentioning
confidence: 99%
“…12, 13 A microfluidic device coupled with functionalities of fluorescence imaging and amperometric detection has been developed to enable the real-time monitoring of the exocytotic events of single SHSY5Y neuroblastoma cells. 14 Sigworth’s group at Yale fabricated poly(dimethyl siloxane) (PDMS) substrates to replace the pipette and successfully recorded single ion channel current from Xenopus oocytes. 15 Fertig and colleagues reported a planar patch-clamp glass chip to record electrical current measure from different cell types in a whole-cell mode.…”
Section: Introductionmentioning
confidence: 99%
“…In these pioneering works exocytosis from chromaffin cells was monitored under conditions of continuous perfusion culture. Although ideal for fundamental molecular biology studies performed over several hours these, and other similar devices,13–15 were not designed for long‐term cell‐based environmental biosensing. In another recent study, the utility of coupling electrochemical and fluorescent techniques for cell‐based biosensing of pesticides was reported 16.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Amatore et al [64] have reported the real-time observation of fluorescence and amperometric measurements of exocytosis events at single biologic cell on transparent indium tin oxide (ITO) microelectrodes(Figure 12). Similar investigations were done using microfluidic configuration[65].…”
mentioning
confidence: 70%